Biocatalysis for the synthesis of pharmaceuticals and pharmaceutical intermediates. Issue 7 (1st April 2018) - Sun, Huihua; Zhang, Hongfang; Ang, Ee Lui; Zhao, Huimin
Graphical abstract: Abstract: Biocatalysis has been increasingly used for pharmaceutical synthesis in an effort to make manufacturing processes greener and more sustainable. Biocatalysts that possess excellent activity, specificity, thermostability and solvent-tolerance are highly sought after to meet the requirements of practical applications. Generating biocatalysts with these specific properties can be achieved by either discovery of novel biocatalysts or protein engineering. Meanwhile, chemoenzymatic routes have also been designed and developed for pharmaceutical synthesis on an industrial scale. This review discusses the recent discoveries, engineering, and applications of biocatalysts for the synthesis of pharmaceuticals and pharmaceutical intermediates. Key classes of biocatalysts include reductases, oxidases, hydrolases, lyases, isomerases, and transaminases.